Biodiversity of the neotropical larginae (Hemiptera: Pyrrhocoroidea: Largidae): Description of a new genus and new species - Melo, María Cecilia (2019)
A new genus of Larginae (Largidae), Parvacinocoris, is described to include a new species from Argentina and Paraguay, and P. stehliki (Doesburg) new combination, a species previously placed in Acinocoris, previously known from Surinam and Venezuela and in this paper recorded also from Brazil, Colombia and Guatemala. This new genus is similar to Acinocoris however it may be separated by the smaller size, the shorter antennae, the immaculate abdominal sterna, the shape of the parameres, and the presence of a pair of hook‐like processes on the aedeagal conjunctiva. Photographs of dorsal and lateral habitus of both sexes as well as the male genitalia of the new species are included.